Effect of fetal liver condition media derived cytokines (IL-6 and Flt-3) on human bone marrow stem cells colony formation. (May 2022) - Bhardwaj, Rashmi; Kumar, Lalit; Chhabra, Deepika; Mohanty, Sujata; Sharma, Atul; Mehra, N.K.; Kochupillai, Vinod
Highlights: Fetal liver conditioned medium (FLCM) was evaluated for the presence of 5 cytokines viz, GM-CSF, SCF, IL-6, Epo, and Flt-3 by ELISA. IL-6 and FL-3 were found to be in maximum samples. IL-6 and Flt-3 are present in considerable amounts in FLCM. IL-6 and Flt-3 are major cytokines responsible for stimulating colonies in normal bone marrow samples. Abstract: Earlier research from our laboratory demonstrated the presence of stimulatory activity of different growth factors in the fetal liver (FL) extracts when collected in a medium known as fetal liver conditioned medium (FLCM) using Enzyme-linked Immunosorbent Assay (ELISA). In the present study, we have assessed two other cytokines viz. IL-6 and FMS like tyrosine kinase-3 (Flt-3) with the help of bioneutralization assay. FLCM was prepared by incubating fetal liver cells with Iscove's Modified Dulbecco's Medium (IMDM) containing 10% fetal bovine serum (FBS) and 10% Phytohemagglutinin and collected after 24hrs, 48hrs, 72 hrs. and on the 7th day of incubation. Clonal cultures were established for 1 X 10 5 normal bone marrow (BM) mononuclear cells (NBM MNC) per plate with methylcellulose medium containing cytokines SCF and EPO. Mean Colony forming units-granulocytes, erythrocytes, macrophages, megakaryocytes (CFU-GEMM) were assessed with and without the addition of FLCM. It was found that FLCM enhanced the number of colonies made by NBM MNCs. Further, cytokines IL-6 and Flt-3, present in FLCM, were bioneutralized with respective anti-cytokine antibodies. Neutralized FLCM was evaluated for the colony-forming potential of CFU-GEMM colonies. The maximum reduction of 42% was seen with 20 ng/ml of anti-IL-6 antibody. Maximum suppression up to 20% was observed with 0.7 ng/ml of anti Flt-3 antibody for CFU-GEMM colonies. Presence of cytokines IL-6 and Flt-3 in FL extracts and their colony stimulatory activity suggests that fetal liver infusion (FLI) may be a valuable alternative for managing BM recovery in certain clinical conditions such as AA.